BEBERAPA FAKTOR YANG MEMPENGARUHI REALISASI PENERIMAAN PAJAK STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA SERPONG - Abdullah - Mubarok (Universitas Pamulang, 2017)
Abstract The purpose of this study was to examine factors :tax penalties and tax audit body effeks on tax revenue in STO Serpong. Sample data is used as the material is data analysis research report tax penalties, the tax inspection bodies and tax revenue from the year 2011-2016 on STO Serpong. The method of data analysis used in this research is descriptive quantitative method. While the statistical analysis used is the classic assumption test, multiple linear regression equation, correlation coefficient, multiple determination, and ujui f t test to determine the relationship and influence of these three variables.The results of the study using multiple linear regression statistical analysis showed the coefficient is positive, While the calculation of multiple correlation coefficient test showed tax penalties (x1) and the tax inspection agency (x2) have influence is in tax revenue (y) on STO Serpong. But in testing f t test and showed no significant effect of tax penalties and tax audit bodies on tax revenue on STO Serpong. Sanctions factors have an influence tax of 71% on the overall Tax Revenues STO Serpong and the rest 29% influenced by other factors not examined by investigators. Keywords: Sanctions Tax, Tax Inspection Board, Tax Revenues